Behavioral addictions and nursing approach - Ayakdaş Dağlı, Dilek; Yüyen, Merve Nur (Journal of Dependence, 2023)
Behavioral addiction is the inability to resist the impulses that cause the person to exhibit behaviors that harm himself or his environment. In recent years, the incidence of behavioral addictions has increased, especially with the pandemic that has affected the world. Although the types of behavioral addictions included as diagnoses in the Diagnostic and Statistical Classification of Mental Disorders (DSM-5) of the American Psychiatric Association are gambling addiction and gaming addiction, it is known that there are many types of behavioral addictions such as technology addiction, food addiction, shopping addiction and relationship addiction. Behavioral addictions may not be seen as a problem because they both have a pleasurable aspect and include activities of daily living. Raising awareness at this stage is an important step. The purpose of this review is to explain nursing approaches towards behavioral addictions that are a part of our lives.